TAXONOMIC KEY TO THE LACESSITTERMES HOLMGREN (TERMITIDAE: NASUTITERMITINAE) FROM SUMATRA - Syaukani Syaukani (Jurnal Natural, 2017)
A taxonomic key based on soldier and worker characters for an open air processional column termites genera, Lacessititermes, was constructed from material collected from Sumatra and adjacent islands from 1998 to 2017. As many as seven species of the genus are taxonomically difficult and complicated. Soldier caste is efective to separate L. piliferus, L. longinsus, L. albipes and L. batavus while mandible characters are efective to separate L. laborator from L. sordidus. Combination of soldier and worker characters are highly useful for identification of Lacessititermes from Sumatra. Keywords: Termite, Lacessititermes, Taxonomy, Sumatra